Introduction of Computer Scoring System for Insurance Decision Making - Sanobar Rajabbaevna Matiyazova (International Journal on Economics, Finance and Sustainable Development, 2022)
The article discusses the need to create a scoring system. The description of the insurance underwriting process and its alternatives - calculating the insurance rating, based on data obtained from the analysis of questionnaires by special scoring system. In this article, the introduction of a scoring system for insurance activities is interpreted as an important part of the socio-economic activities of the insurance company. The current situation with the scoring system is analyzed and the legal framework is considered. The views of leading scholars on this have been analyzed. Suggestions and recommendations for the introduction of a scoring system for insurance activities have also been formulated.